ENVIRONMENTAL BIOTECHNOLOGY - TOOLS FOR A SUSTAINABLE FUTURE? - Palomino, Alfredo (2001)
Throughout history, man has exploited nature to meet his needs. In the last tew decades it has become evident that uncontrolled exploitation is unsustainable - anthropogenic pollution and the depletion of non-renewable resources cannot continue it we are to avoid catastrophic events in the coming century. The scope of such environmental problems is broad and their nature complex. This paper discusses the extent to which biotechnology can contribute to the solutions of our environmental problems, and the challenges that tace us in developing and implementing both existing and new biotechnologies.